G2∕C1 Hermite interpolation by planar PH B-spline curves with shape parameter. (November 2021) - Albrecht, Gudrun; Beccari, Carolina Vittoria; Romani, Lucia
Abstract: We solve the problem of G 2 ∕ C 1 Hermite interpolation (i.e. interpolation of prescribed boundary points as well as first derivatives and curvatures at these points) by planar quintic Pythagorean Hodograph B-spline curves with one free interior knot which acts as a shape parameter. We present conditions on the data ensuring the existence of solutions. Finally, we illustrate the influence of the interior knot on the shape of the resulting interpolant and on the values of the absolute rotation index or the bending energy.